Perlindungan Keamanan Manusia Australia Melalui Kebijakan Turn Back The Boat Pada Masa Pemerintahan Tony Abbott - Ulfa, Nadrah; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Australia experienced a significant increase in refugee arrivals from 2008 to 2012 with the highest number of refugee arrivals occurring in 2012. Therefore, during the reign of Tony Abbott, Australia implemented the ‘turn back the boat’ policy to prevent refugees and asylum seekers from entering Australian waters. The aim of this research is to explain the causes of Australia implementing the ‘turn back the boat’ policy. In the concept of human security there are seven aspects of security namely economic security, food security, health security, environment security, personal security, community security, and political security. Therefore, the causes of Australia implemented the ‘turn back the boat’ policy because Australian human security is threatened due to the arrival of refugees and asylum seekers, especially in the aspects of environment security and personal security